Bibliometric visualization of literature on Information and Communications Technology (ICT) in education - Loh, Yoke Ling; Mohd Haniff Mohd Tahir; Lim, Chsing Chsing (Penerbit Universiti Kebangsaan Malaysia, 2023)
Information and communication technology (ICT) in education, also known as education technology, is an important component of SDG 4's goal of improving educational quality. This Bibliometric study examines research patterns over time using the term "education technology." Three research questions are prioritised: (1) What is the current publication trend in EduTech? (2) What are the most popular themes among EduTech scholars? (3) What is the current citation pattern of EduTech publications? The methodology of this study uses bibliometric analysis with quantitative approach (document trend statistics) in the data scopus.com database for the years 1946 to 2022. The study's findings showed the number of publications on this education technology has increased since 2005, and this trend is expected to continue, with a recent notable theme being a focus on methodology studies, particularly in the field of health education. Furthermore, the most cited document was an article about activity design by Koehler et al., (2005), and the most cited author was Jonathan Michael Spector. Apart from Europe, Asian countries such as Malaysia and China are currently conducting more EduTech research. The implications of this study provide a positive outlook on the future of multiple educational technology research projects. Global pressures such as the pandemic and the need for IR4 are having an impact on the explosion of educational technology in society, government, industry, the environment, and academia.